Cognitive Impairment in Individuals With Spinal Cord Injury: Findings of a Systematic Review With Robust Variance and Network Meta-analyses. (18th October 2022) - Sandalic, Danielle; Craig, Ashley; Tran, Yvonne; Arora, Mohit; Pozzato, Ilaria; McBain, Candice; Tonkin, Helen; Simpson, Grahame; Gopinath, Bamini; Kaur, Jasbeer; Shetty, Sachin; Weber, Gerard; et al.
Abstract : Background and Objectives: Estimates of the prevalence (10%–60%) of cognitive impairment in individuals with spinal cord injury (SCI) are too broad, and which domains of cognition are most affected is unclear. We performed a meta-analysis to investigate impairments across domains of cognitive functioning to provide a nuanced picture of research conducted to date into cognitive impairment after SCI. Methods: Results of peer-reviewed studies published in English between 1980 and 2021 comparing ≥20 participants with SCI with able-bodied controls were synthesized using meta-analysis. The primary outcomes were neurocognitive test scores categorized into 5 cognitive domains as listed in the Diagnostic and Statistical Manual of Mental Disorders: Complex Attention, Executive Functioning, Learning and Memory, Language, and Perceptual Motor Function. Two researchers independently assessed and verified extracted data to comply with meta-analytic reporting guidelines. Robust variance estimation meta-analysis was conducted to determine an overall pooled effect size across all cognitive domains using data extracted from studies. Using network meta-analysis, we synthesized eligible studies and made comparisons with the 5 domains of cognitive functioning serving as the outcomes and SCI as the condition. Results: Of 4, 783 potential studies, 13 met final inclusion criteria. Studies met 6 of 8 quality assessment criteria generally. Results suggested that adults with SCI experience reduced cognitive functioning (effect size: −0.84; 95% CI −1.24 to −0.44, p < 0.001) compared with able-bodied individuals, with deficits mostly in attention (g = −0.64; 95% CI −0.92 to −0.38) and executive functioning (g = −0.61, 95% CI −0.89 to −0.04). Publication bias and high heterogeneity (I 2 : 86%) qualify these findings and highlight the need to improve research methods in this area. Discussion: Adults with SCI seem more likely than adults who are able-bodied to display cognitive impairments mostly in areas of attention and executive functioning. Research practices must become consistent to reduce heterogeneity so that the validity and reliability of the results of future studies into cognitive impairment after SCI improves.